Vpliv parodontalne bolezni na prezgodnji porod in nižjo porodno težo novorojencev - Dahmane, Raja (Obzornik zdravstvene nege, 2011)
Preterm birth and low birth weight represent major social and economic public health problems. Preterm birth occurs in 6% of births in Slovenia which is about 1000 children per year. Known risk factors for spontaneous preterm birthinclude a previous preterm birth, high or low body mass index, alcohol consumption during pregnancy, ethnicity (African American), smoking, fetal fibronektin, inflammatory mediators such as interleukin-6 (IL-6) and prostaglandin E2 (PGE2) and intrauterine infections. There has recently been afocus on periodontal infection - periodontal disease as a risk factor for preterm birth. The findings indicated that periodontal diseases in the pregnant mother significantly increase the risk of subsequent preterm birth orlow birth weight due to the systemic increase of pro- inflammatory cytokines, which reduce the viability of the placenta and cause premature contractions of the uterus. Successful initial periodontal treatment with scaling and root planning is associated with a decreased incidence of spontaneous preterm birth and low birth weight. Since periodontal disease is very common in Slovenia, it is recommended that obstetricians are provided also with information concerning the childbearing womenćs oral health and explain them the impact of periodontal disease on the fetus and measures to prevent gingival inflammation.
Keywords: Dejavniki tveganja; Dental Plaque; human pregnancy; Infant, Low Birth Weight; Labor, Premature; Microbiology; Nosečnost; Novorojenček z nizko porodno težo; Parodontalne bolezni; Periodontal Diseases; Porod prezgodnji; Pregnancy; prezgodnji porod; Risk Factors; Zobni plak